Three new species of longhorned beetles (Coleoptera: Cerambycidae) with notes on additional taxa - Nearns, Eugenio H.; Swift, Ian P.; Santos-Silva, Antonio (Zootaxa, 2023)
The differences between Methia enigma Martins, 1981 and M. argentina Bruch, 1918 (Cerambycinae: Methiini) are discussed, and a new country record for the latter is provided. Sexual dimorphism in Pseudosparna Mermudes and Monné, 2009 (Lamiinae: Acanthocinini) is reported for the first time, and two new species of Pseudosparna (Lamiinae: Acanthocinini) are described from Panama: Pseudosparna dimitrisi sp. nov. and Pseudosparna marilenae sp. nov. The female of Pseudosparna mantis Devesa & Santos-Silva, 2020 is described for the first time. Eranina dariae sp. nov. (Lamiinae: Hemilophini) is described from French Guiana. The type locality of Bisaltes (Bisaltes) bimaculatus Aurivillius, 1904 (Lamiinae: Apomecynini) is reported, and a new country record is provided for the species. Aerenea subsulcicollis Breuning, 1948 (= A. sulcicollis subsulcicollis) (Lamiinae: Compsosomatini) is synonymized with A. sulcicollis Melzer, 1932, and a new country record is provided. A new state record is provided for Schmidarius kondratieffi Santos-Silva, Heffern, Botero & Nascimento, 2020 (Lamiinae: Hemilophini). Tucumaniella Breuning, 1943 (Apomecynini) is synonymized with Cacostola Fairmaire & Germain, 1859 (Onciderini), and Tucumaniella brevipes Breuning, 1943 is synonymized with Cacostola volvula (Fabricius, 1787).